How to Deal with Negative Publicity: the Importance of Consumer Involvement - Celso Augusto de Matos; Ricardo Teixeira Veiga (BAR: Brazilian Administration Review, 2005)
Negative information about companies can have a harmful effect on consumer perceptions. However, few studies investigate how consumers process negative publicity and how companies should react to it. In order to examine this question, two experiments were carried out: first, a laboratory experiment which tests how consumers process two different types of negative publicity (product attributes or company values); second, a field experiment comparing three different responses (no answer, denial/reduction of offensiveness and corrective action) given by the company affected by the negative publicity. Results from the first study confirm the detrimental effect of negative publicity on consumer attitudes, indicate that consumers have a higher level of involvement with the message when it is concerned with the company’s values and suggest a moderating role of the product involvement on the influence of negative information on corporate image. The second study extends these findings by identifying different options for company reactions from literature and testing them empirically. Results suggest again the involvement variable as a moderator, now on the influence of companyreaction on product image.